Education and language policy in colombia: exploring processes of inclusion, exclusion, and stratification in times of global reform (2009)
This paper examines the National Bilingual Program in connection with other education and language reforms in Colombia and some of the processes of inclusion, exclusion, and stratification that accompany current school reforms. The author outlines some patterns that have accompanied language innovations in the country and highlights some interconnected processes that seem to be favored in international reform and are reflected in current national policy agendas; namely, the externalization of policy discourses; the instrumentalization of languages; the stratification of groups, languages and cultures; and the standardization and marketization of foreign language teaching and learning. This paper attempts to demonstrate that processes of inclusion, exclusion and stratification through schooling are favored not only through the overt exercise of power and control, but also through the introduction of new discourses, policies, and practices. Key words: National Bilingual Program, language policies, education reform Este artículo analiza el Programa Nacional de Bilingüismo en conexión con otras reformas educativas y lingüísticas promovidas en Colombia y distintos procesos de inclusión, exclusión y estratificación que las acompañan. El autor esboza algunos patrones que han acompañado distintas reformas educativas y lingüísticas en el país y diversos fenómenos reportados a nivel internacional que ahora se pueden evidenciar en Colombia. Estos incluyen: la “externalización” de discursos, la instrumentalización de las lenguas, la estratificación de grupos, idiomas y culturas, y la estandarización y marketización de las lenguas extranjeras. Este artículo busca demostrar que los procesos de inclusión, exclusión, y estratificación social a través de la escuela son favorecidos no solamente a través del ejercicio del poder y el control de parte del gobierno, sino también mediante la introducción de nuevos discursos, políticas, y practicas escolares. Palabras clave: Programa Nacional de Bilingüismo, políticas lingüísticas, reforma educativa